2020
DOI: 10.1002/14651858.cd013399.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis of thromboembolism during therapy with asparaginase in adults with acute lymphoblastic leukaemia

Abstract: Cavanna L, et al. Nadroparin for the prevention of thromboembolic events in ambulatory patients with metastatic or locally advanced solid cancer receiving chemotherapy: a randomised, placebo-controlled, double-blind study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 153 publications
0
9
1
1
Order By: Relevance
“…of low‐molecular‐weight heparin (LMWH) in preventing venous thromboembolism (VTE) in patients receiving intensified asparaginase therapy for acute lymphoblastic leukaemia (ALL). In particular, Tong notes an apparent discrepancy between the findings of this study and the recent Cochrane review 3 of the same area, which concluded that there was insufficient evidence of appropriate quality to draw definitive conclusions. Indeed the review concluded there was a need for randomised controlled trials.…”
contrasting
confidence: 64%
See 1 more Smart Citation
“…of low‐molecular‐weight heparin (LMWH) in preventing venous thromboembolism (VTE) in patients receiving intensified asparaginase therapy for acute lymphoblastic leukaemia (ALL). In particular, Tong notes an apparent discrepancy between the findings of this study and the recent Cochrane review 3 of the same area, which concluded that there was insufficient evidence of appropriate quality to draw definitive conclusions. Indeed the review concluded there was a need for randomised controlled trials.…”
contrasting
confidence: 64%
“…Tong makes a number of statistical points regarding the methods of analysis: it is hard to argue with calls for time‐to‐event analyses and adjustments for multiple testing (especially where there are so few events). Addressing the Cochrane review conclusions, 3 it is understandable to be unconvinced by historically controlled database analyses for a number of reasons, and the Sibai et al . report 2 can act as an indicator of why such evidence can be difficult to interpret.…”
mentioning
confidence: 99%
“…Other risk factors are older age and the number of chronic comorbidities. 51,53 Risk assessment models in leukemia are as follows:…”
Section: Acute Leukaemiamentioning
confidence: 99%
“…This is interesting in particular as very recently Rank et al published their Cochrane review stating that from the currently available evidence, they could not ascertain if thromboprophylaxis used for adults suffering from ALL (and treated with asparaginase-based regimens) is associated with clinical benefits and acceptable toxicity. 11 Sibai et al acknowledged that their sample size was limited for identifying predictors and prognostic factors. They found that T-phenotype ALL was associated with VTE development.…”
mentioning
confidence: 99%
“…This is interesting in particular as very recently Rank et al . published their Cochrane review stating that from the currently available evidence, they could not ascertain if thromboprophylaxis used for adults suffering from ALL (and treated with asparaginase‐based regimens) is associated with clinical benefits and acceptable toxicity 11 …”
mentioning
confidence: 99%